2015
DOI: 10.1152/ajpregu.00142.2015
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-derived ET-1 and the development of renal injury

Abstract: De Miguel C, Pollock DM, Pollock JS. Endothelium-derived ET-1 and the development of renal injury. Am J Physiol Regul Integr Comp Physiol 309: R1071-R1073, 2015. First published May 20, 2015 doi:10.1152/ajpregu.00142.2015.-The role of the vasoactive peptide endothelin-1 (ET-1) in renal injury is not fully understood. In this review, we examine the genetic models available to understand the autocrine/paracrine mechanisms by which ET-1 leads to renal injury and propose the working hypothesis that endothelium-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Using a model of mouse lacking ET-1 specifically in vascular endothelial cells (VEET KO mice), these investigators demonstrated that the lack of endothelium-derived ET-1 not only attenuated proximal tubular injury in response to I/R, but also decreased inflammatory and oxidative stress responses. These results suggest that ET-1 produced by the vascular endothelium acts in a paracrine manner on neighboring epithelial cells to induce renal injury [32]. Results from our own laboratory support these observations.…”
Section: Introductionsupporting
confidence: 63%
“…Using a model of mouse lacking ET-1 specifically in vascular endothelial cells (VEET KO mice), these investigators demonstrated that the lack of endothelium-derived ET-1 not only attenuated proximal tubular injury in response to I/R, but also decreased inflammatory and oxidative stress responses. These results suggest that ET-1 produced by the vascular endothelium acts in a paracrine manner on neighboring epithelial cells to induce renal injury [32]. Results from our own laboratory support these observations.…”
Section: Introductionsupporting
confidence: 63%
“…Moreover, data from our laboratory has shown a protective role of ET B receptor activation in tunicamycin-induced renal tubular apoptosis. 60 Thus, our results suggest that the albuminuria observed in HbSS mice treated with the dual ET A/B receptor antagonist is a combination of glomerular and tubular injury or dysfunction.…”
Section: Discussionmentioning
confidence: 57%
“…ET-1 is a 21 amino acid peptide that is described as a vasoconstrictor, autocrine/paracrine mitogen and suppressor of apoptosis in the human body (de Miguel et al 2015, Shichiri et al 2000, Tsai et al 2015.…”
Section: Introductionmentioning
confidence: 99%